Mortality of farmers and farmers' wives in England and Wales 1979-80, 1982-90. Issue 11 (November 1996) - Inskip, H; Coggon, D; Winter, P; Pannett, B
Abstract : OBJECTIVES: To examine the mortality patterns of male and female farmers and farmers' wives in England and Wales. METHODS: Information on all deaths in England and Wales at ages 20-74 during the periods 1979-80 and 1982-90 was obtained from the Office of Population Censuses and Surveys. Proportional mortality ratios (PMRs) and proportional cancer mortality ratios (PCMRs) were used to compare the mortality of farmers with that of the general working population, and of farmers' wives with wives of all working men. RESULTS: Farmers and farmers' wives had high mortality from accidents and suicide and from certain respiratory diseases. Mortality from hernia was also raised. Deaths from cancer were generally below expectations, but the PMR for prostatic cancer was 112 (95%CI 106-118). The PMRs and PCMRs for oesophageal cancer were significantly increased in male farmers from two counties where cider is produced. CONCLUSIONS: The occupational hazards of farming continue to be associated with excess mortality, and most of the risks extend also to farmers' wives. Action is needed to reduce deaths, particularly from accidents and suicide.